Pengaruh Supervisi dan Kepercayaan Diri terhadap Kepuasan Kerja Guru SMKN di Jakarta Timur - Annas Firdausi (SAP (Susunan Artikel Pendidikan), 2018)
This study aims to determine how much influence of supervision by supervisor and teachers’ self-confidence in teachers to job satisfaction. The sample of research is 230 teachers from 571 people with civil servant teacher status, with simple random sampling technique, thus representing teacher population at 14 SMKN in East Jakarta administration area. The type of data used is cross section data obtained by using questionnaire. Result of calculation of path analysis obtained result: (1). supervision affects the direct job satisfaction increase of 32.5%, and through self-confidence of 6.1%. This means the influence of supervision and self-confidence together to increase job satisfaction by 38.6%. (2). Self confidence directly affects the increase in job satisfaction by 8.8%, and indirectly through supervision of 6.1%, which means the amount of influence sel-confidence and supervision to increase job satisfaction of 14.9%. (3). Supervision has a direct effect to increase self-confidence by 12.8%. Thus, the three results of the above analysis can be concluded that: (a). Increased supervision leads to increased job satisfaction, (b). Increased self-confidence leads to increased work satisfaction, and (c). Increased supervision leads to increased self-confidence.